NEW POSSIBLE MULTIDIMENSIONAL MODELS FOR CLASSIFICATION OF THE BASIC LEVEL OF PISTOL SHOOTING SKILL - Dopsaj, Milivoj; Marković, Stefan; Prebeg, Goran (NBP. Nauka, bezbednosti, policija, 2020)
The aim of this paper was to provide a possible methodological solution for monitoring of the marksmanship training progress and evaluation of the level of shooting skill acquisition with service pistol CZ99. The second aim was the idea of development of a screening model for gender-dependent classification of the police personal, other security personnel and sport-oriented personnel in relation to their basic marksmanship skill. The research sample included a total of 83 participants (Men = 53, Women = 30) initially divided into four qualitative categories according to the personal shooting experience and shooting skill level. The applied principal component analysis has revealed a highly stable structure of the component matrix of the extracted factor. The following variables had the highest descriptive value in relation to the shooting skill in the respective samples regardless of distance: Men - an averaged value of the hit circles on the target and rounds fired, the index of efficiency considering precision and a coefficient of variation of hit circle achieved during the shooting at the target; Women - an averaged value of the hit circles on the target and rounds fired, the index of efficiency considering precision, a coefficient of variation of hit circle achieved during the shooting at the target and the index of efficiency considering accuracy. On the basis of the obtained results highly statistically significant (p ≤ 0.000) specific multidimensional models were developed which enabled statistically significant classification of the participants relative to the pistol shooting skill classification. The accuracy of the defined equation model for estimation of shooting skill score classification was 59.7 and 61.5% for men and 68.6 and 68.0% for women in relation to the examined shooting distances of 6 and 10 m, respectively.
Keywords: Shooting skill, police officer, multidimensional model, pistol shooting training.